Emotion-Driven Leadership Programme Curricular in TVET and Higher Education - Ahmad, Zaiha; Ibrahim, Zuraeda; Azmi, Nur Nafishah; Tsuchiya, Toshio; Mohd. Lokman, Anitawati (Journal of Technical Education and Training, 2025)
This study aims to redefine the curricula for leadership in Technical and Vocational Education and Training (TVET) and higher education as dynamic and emotionally engaging systems, utilizing the frameworks of Kansei Engineering and the LEIQ™ model. It explores how emotion-driven strategies can enhance leadership readiness, addresses implementation challenges such as cultural adaptability and resource allocation, and highlights opportunities for scalable, evidence-based curricular reforms. Using a mixed-methods approach, the research analyzed three leadership programmes involving 150 participants and utilized a 28-item Kansei checklist. Factor Analysis (FA) and Partial Least Squares (PLS) were employed to identify the key emotional factors involved. The results revealed two dominant emotional dimensions: Excitement and Confidence. Additionally, the researchers identified 15 programme components with 41 attributes that significantly impact these emotional responses. Through the LEIQ™ model, the researchers examined the challenges and motivations surrounding leadership development. This exploration led to five key implementation strategies: designing programmes around emotional clusters, optimizing programme management, enhancing motivation, developing a balanced curriculum, and focusing on student-centered development. The research culminated in developing a framework for designing Emotionally Evocative Leadership Programs. This framework offers practical guidelines for incorporating emotional elements into leadership programmes while addressing technical competencies and emotional intelligence development. It provides a systematic approach that can be applied across various leadership contexts. These findings deepen the research understanding of emotions’ role in leadership development and equip educators with evidence-based strategies for creating more engaging and effective leadership programs. The study emphasizes the importance of balancing emotional intelligence with traditional leadership development methods, ultimately supporting a more holistic approach to nurturing future leaders in educational settings. This work contributes to the transformation of education by establishing emotional intelligence as a foundational pillar of leadership development for the 21st century.